The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1038/sj.cdd.4400741
|View full text |Cite
|
Sign up to set email alerts
|

The role of p53 in neuronal cell death

Abstract: The p53 tumor suppressor gene is a sequence-specific transcription factor that activates the expression of genes engaged in promoting growth arrest or cell death in response to genotoxic stress. A possible role for p53-related modulation of neuronal viability has been suggested by the finding that p53 expression is elevated in damaged neurons in acute models of injury such as ischemia and epilepsy and in brain tissue samples derived from patients with chronic neurodegenerative diseases. Moreover, the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(105 citation statements)
references
References 158 publications
5
95
1
Order By: Relevance
“…Activation of p53 has been implicated in excitotoxic neuronal cell death (Morrison and Kinoshita 2000). Moreover, it has also been observed that p53 is activated under hypoxic conditions in vitro (Stempien-Otero et al 1999) and in peri-ischemic regions of an animal model of focal stroke (Chopp et al 1992;Li et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of p53 has been implicated in excitotoxic neuronal cell death (Morrison and Kinoshita 2000). Moreover, it has also been observed that p53 is activated under hypoxic conditions in vitro (Stempien-Otero et al 1999) and in peri-ischemic regions of an animal model of focal stroke (Chopp et al 1992;Li et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that p53, at least in certain tissues, is necessary for cell death induction by ischemia. 31 However, different levels of p53 expression do not seem to be involved in the resistance to ischemia of p66…”
Section: P66mentioning
confidence: 99%
“…In the central nervous system, however, replacement neurons are only available marginally if at all (3,4), putting a greater burden on the survival mechanisms of mature neurons. Determining how neurons are able to survive manyfold longer than the average mammalian cell poses one of the great challenges of research in neurobiology (5,6). This question is more than of academic interest because failure to survive, either during the developmental process, during aging, or upon exposure to potentially lethal insults, is the basis for innumerable neurodegenerative conditions.…”
mentioning
confidence: 99%